2013
DOI: 10.1007/s40261-013-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of 5-Grass Pollen Tablets Versus Placebo in the Treatment of Allergic Rhinitis in Adults

Abstract: BackgroundAllergen immunotherapy (AIT) is aimed at modifying the immune response to a causative allergen, thereby reducing clinical symptoms and symptomatic medication intake and improving quality of life. Long-term AIT research has led to the development of 5-grass pollen tablets, currently indicated for the treatment of grass pollen-induced allergic rhinitis (AR).MethodsA post-hoc analysis was conducted using the Average Adjusted Symptom Score (AAdSS) to compare the effect of treatment of AR with 5-grass pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…A clinically significant improvement was a gain of ‡1.45 points in the AAdSS. In comparison to placebo, results indicate that OA is a cost-effective treatment option for adults with AR and a medium or high AAdSS, providing a benefit of 0.127 or 0.143 QALYs, respectively, with corresponding costs of e1024 and e1035 per QALY [67]. These findings may have important implications when deciding on the most appropriate management strategy for patients with AR who manifest moderate-to-severe symptoms.…”
Section: Health Economics Profilementioning
confidence: 91%
See 1 more Smart Citation
“…A clinically significant improvement was a gain of ‡1.45 points in the AAdSS. In comparison to placebo, results indicate that OA is a cost-effective treatment option for adults with AR and a medium or high AAdSS, providing a benefit of 0.127 or 0.143 QALYs, respectively, with corresponding costs of e1024 and e1035 per QALY [67]. These findings may have important implications when deciding on the most appropriate management strategy for patients with AR who manifest moderate-to-severe symptoms.…”
Section: Health Economics Profilementioning
confidence: 91%
“…A post hoc analysis of data from the VO34.04 and VO53.06 clinical trials used the AAdSS to compare AR treatment with OA versus placebo, and its cost-effectiveness [67]. A clinically significant improvement was a gain of ‡1.45 points in the AAdSS.…”
Section: Health Economics Profilementioning
confidence: 99%
“…Studies show the economic benefit in the use of AIT [93][94][95]. Hankin et al did a retrospective [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008][2009] Florida Medicaid claims analysis comparing mean 18-month health care costs of adult and pediatric patients with newly diagnosed AR who received de novo SCIT and were continuously enrolled for 18 months or more versus matched control subjects not receiving SCIT [96].…”
Section: Most Important: What Does the Patient Prefer!mentioning
confidence: 99%
“…It was concluded that Oralair™ was a cost‐effective and cost‐saving alternative to Grazax™ and SCIT in Germany . However in a study conducted in Italy, Oralair™ was found to be cost ineffective in patients with mild allergic rhinitis .…”
Section: Discussionmentioning
confidence: 99%